2018
DOI: 10.1177/2472555218763310
|View full text |Cite
|
Sign up to set email alerts
|

ΔF508-CFTR Modulator Screen Based on Cell Surface Targeting of a Chimeric Nucleotide Binding Domain 1 Reporter

Abstract: The most common cystic fibrosis–causing mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) is deletion of phenylalanine at residue 508 (ΔF508). The ΔF508 mutation impairs folding of nucleotide binding domain 1 (NBD1) and interfacial interactions of NBD1 and the membrane spanning domains. Here, we report a domain-targeted screen to identify ΔF508-CFTR modulators that act on NBD1. A biochemical screen for ΔF508-NBD1 cell surface expression was done in Madin–Darby canine kidney cells expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…F508del—and a number of other processing mutations—however, are known to also suffer from gating defects [ 54 ]. To account for this, screening assays looking directly at the trafficking of mutant CFTR proteins have since also been developed [ 128 , 129 , 130 , 131 , 132 ]. Recently, a fluorescence resonance energy transfer (FRET) based HTS platform was developed to evaluate the folding of nascent, ribosome-bound NBD1 mutants to specifically identify compounds able to restore the conformation of NBD1 [ 133 ].…”
Section: Cftr Causal Therapiesmentioning
confidence: 99%
“…F508del—and a number of other processing mutations—however, are known to also suffer from gating defects [ 54 ]. To account for this, screening assays looking directly at the trafficking of mutant CFTR proteins have since also been developed [ 128 , 129 , 130 , 131 , 132 ]. Recently, a fluorescence resonance energy transfer (FRET) based HTS platform was developed to evaluate the folding of nascent, ribosome-bound NBD1 mutants to specifically identify compounds able to restore the conformation of NBD1 [ 133 ].…”
Section: Cftr Causal Therapiesmentioning
confidence: 99%
“…Substantiating their potential, all four compounds were validated as CFTR potentiators through short-circuit current recordings performed within a comprehensive Phe508del-CFTR potentiator assay. 43…”
Section: Overview Of Small Molecule Cftr Activatorsmentioning
confidence: 99%
“…Substantiating their potential, all four compounds were validated as CFTR potentiators through short-circuit current recordings performed within a comprehensive Phe508del-CFTR potentiator assay. 43 Yang et al first reported the CFTR-activating activity of 1,4-dihydropyridine structural compounds through HTS. 40 Pedemonte et al identified several antihypertensive 1,4-dihydropyridines (DHPs) such as nifedipine, nicardipine, nimodipine, isradipine, nitrendipine, felodipine, and niguldipine as potential ΔF508-CFTR activators (Fig.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…Thiophenes moiety emerged again in a study that was specifically focused on the NBD1 domain of CFTR. [51] Instead of using the whole CFTR protein, the authors designed a special construct consisting of NBD1, carrying the Phe508del mutation, fused to CD4 transmembrane domain and an extracellular horseradish peroxidase (HRP) reporter. Using luminescence, a library of 20,000 compounds was screened to find novel correctors.…”
Section: Thiophenesmentioning
confidence: 99%